Psycholinguistic Peculiarities of Teaching Foreign Languages Children of Pre-School Age: Analysis of Polish Experience - Oleksandra Yankovych; Kateryna Binytska; Larysa Zdanevich (Pedagogical Discourse, 2019)
The article deals with the organization of foreign language education of children in pre-school educational institutions of Poland. The legislative grounds for compulsory teaching of foreign languages to pre-school children have been outlined: the order of the Ministry of Public Education of Poland on May 30, 2014, according to which the amendments to the Pre-School Education Program were introduced. It is emphasized that Poland is one of the three European states that were the first to introduce in pre-school education the study of foreign languages as a compulsory component.It is shown that the introduction of compulsory study of a foreign language in pre-school establishments in Poland is accompanied by scientific researches in the field of theoretical-methodological principles of early foreign language education of children. The expediency of the early start of the foreign language in Poland is grounded on the basis of the psychological, physiological readiness of 3-5 year-old children: the development of sensory organs, mental functions, in particular memory, thinking, ability of the child to concentrate attention (up to 30 minutes), distinguish between sounds, the words of native and foreign languages, colors and shades, absorb intonation.The peculiarities of early foreign language education in Poland have been defined, the purpose of which is the formation of communicative-speech competencies, cultural sensitivity, implementation of multicultural education, individual development of children, as well as formation of motivation to study foreign languages in the future. The directions of realization of the ideas of Polish experience in the institutions of pre-school education of Ukraine have been defined: development of author’s methods of communication in a foreign language; assessment of educational achievements of children, in which the leading role belongs to the recognition of the child’s success; carrying out scientific researches on the expediency of using certain forms, methods, means of teaching at each stage of development of children of pre-school age.